Konseptualisasi White Friday Sebagai Model Pencegahan Bullying - Khairo, Fatria; Busroh, Firman Freaddy; Oktaviyani, Henny (Lex Stricta : Jurnal Ilmu Hukum, 2025)
Bullying among junior high school students remains a significant concern that negatively affects their psychological, social, and academic development. A holistic preventive approach is necessary to cultivate school programs and cultures that foster positive behavior. The conceptualization of the White Friday program emerges as a preventive model designed to build a more inclusive, peaceful, and character-oriented school environment. This model is grounded in routine activities that promote empathy, respect for diversity, and stronger interpersonal connections among school members. Through literature-based analysis, the White Friday program is reviewed from the perspective of character education and the social-ecological theory, which emphasizes collective participation in preventing aggressive behavior. The implementation of this program may include weekly kindness campaigns every Friday, counselor involvement, peer-support strengthening, and fostering healthy communication patterns. Appreciative and reflective activities are also integrated to develop a culture of mutual respect. This conceptual framework is expected to establish a safe climate that enables students to build competence and well-being. The findings indicate that the White Friday program has the potential to become an adaptive, sustainable, and contextually relevant preventive strategy for schools. It not only reduces bullying incidents but also enhances positive character development and psychosocial welfare. Therefore, White Friday can serve as an innovative model for bullying prevention at  junior high schools